A systematic review of self-management interventions for children and youth with physical disabilities. (February 2014) - Lindsay, Sally; Kingsnorth, Shauna; Mcdougall, Carolyn; Keating, Heather
ABSTRACT Purpose: Evidence shows that effective self-management behaviors have the potential to improve health outcomes, quality of life, self-efficacy and reduce morbidity, emergency visits and costs of care. A better understanding of self-management interventions (i.e. programs that help with managing symptoms, treatment, physical and psychological consequences) is needed to achieve a positive impact on health because most children with a disability now live well into adulthood. Method: A systematic review of self-management interventions for school age youth with physical disabilities was undertaken to assess their effectiveness. Comprehensive electronic searches using international web-based reference libraries were conducted for peer-reviewed and gray literature published between 1980 and January 2012. Eligible studies examined the effectiveness of self-management interventions for children and youth between 6 and 18 years of age with congenital or acquired physical disabilities. Studies needed to include a comparison group (e.g. single group pre/post-test design) and at least one quantifiable health-related outcome. Results: Of the 2184 studies identified, six met the inclusion criteria; two involved youth with spina bifida and four with juvenile arthritis. The majority of the interventions ran several sessions for at least 3 months by a trained interventionist or clinician, had one-to-one sessions and meetings, homework activities and parental involvement. Although outcomes varied between the studies, all of the interventions reported at least one significant improvement in either overall self-management skills or a specific health behavior. Conclusions: While self-management interventions have the potential to improve health behaviors, there were relatively few rigorously designed studies identified. More studies are needed to document the outcomes of self-management interventions, especially their most effective characteristics for children and youth with physical disabilities. Implications for Rehabilitation There is some evidence to suggest that self-management interventions for children and youth with spina bifida and arthritis can improve self-management behaviors and health outcomes. Parents' involvement should be considered in encouraging self-management behaviors at different stages of their child's development. Much work is needed to explore the longer term implications of self-management interventions for youth with physical disabilities as well as the impact on health care utilization.